Symbiotic Relationships between Integrated Project Delivery (IPD) and Trust. Issue 3 (2nd July 2016) - Pishdad-Bozorgi, Pardis; Beliveau, Yvan J.
ABSTRACT: As an emerging trend, Integrated Project Delivery (IPD) aims to address the issue of mistrust by using a relational contracting approach. Given that trust demonstrates a perceived reliability of an individual through time, one may question the role that a project delivery or contract could possibly play in building trust. The objective of this research is to analyze the relationship between trust and IPD. The research findings indicate that IPD and trust have a symbiotic relationship. While committing to an IPD arrangement requires an established trust, the IPD arrangement also further promotes trust. Committing to an IPD arrangement requires trust due to the existence of shared risks and rewards model and waivers of liabilities provision. On the other hand, IPD organizational and contractual principles further promote system-based trust, and IPD communication and behavioral principles further promote cognition-based trust. This manuscript contributes to the body of knowledge by providing insights into the symbiotic relationship between IPD and trust and identifying the trust-building attributes in construction contracting and more specifically IPD.